Evaluation of the Ocular Surface Disease Index Questionnaire as a Discriminative Test for Clinical Findings in Dry Eye Disease Patients. (2nd September 2019) - Yazdani, Mazyar; Chen, Xiangjun; Tashbayev, Behzod; Utheim, Øygunn A.; Ræder, Sten; Hua, Yanjun; Eidet, Jon R.; Stojanovic, Aleksandar; Dartt, Darlene A.; Utheim, Tor P.
ABSTRACT: Purpose : To investigate to what extent the OSDI can be utilized as a discriminative test for clinical findings. Methods : One thousand and ninety patients with dry eye disease (DED) were consecutively included and examined for osmolarity, tear film break-up time (TFBUT), ocular protection index (OPI), ocular surface staining (OSS), Schirmer I test (ST), meibum expressibility (ME), meibum quality (MQ), and diagnosis of meibomian gland dysfunction (MGD). Receiver-operating characteristic curve (ROC) analysis considering optimum balanced sensitivity and specificity (close to 50%) was used for assessment. Results : The present study on more than 1, 000 patients indicates that the OSDI in the ROC curve analysis is a poor discriminator of pathological scores for TFBUT ≤ 5 (AUC = 0.553; p = .012) and ≤10 s (AUC = 0.608; p = .002), OSS ≥ 3 (AUC = 0.54; p = .043), ST ≤ 5 (AUC = 0.550; p = .032) and ≤10 mm/5 min (AUC = 0.544; p = .016), and ME ≥ 1 (AUC = 0.594; p = <0.001). Pathological scores for osmolarity >308 and >316 mOsm/L, OPI, OSS > 1, MQ, and MGD could not be discriminated by OSDI ( p > .05). Conclusion : Cut-off values for the OSDI can be defined to discriminate pathological TFBUT (≤5 and ≤10), OSS (≥3), ST (≤5 and ≤10) and ME, however, the discriminability was low. Our comprehensive study emphasises the importance of taking both symptoms and signs into account in DED management.